1976
DOI: 10.1159/000158090
|View full text |Cite
|
Sign up to set email alerts
|

Modification by Temperature of the Response of Isolated Aorta to Stimulatory Agents and Transmural Stimulation

Abstract: Contractile responses of helically-cut strips of the rabbit aorta to drugs, ions and transmural electrical stimulation were compared at different temperatures of the bathing medium, the response at 37 °C being taken as control. The dose-response curve of norepinephrine was moved to the right and downward by lowering the temperature from 37 to 25 °C and by raising temperature to 40 °C. Responses to transmural neural stimulation at frequencies of 5 and 20/sec were attenuated at 25 °C, the attenuation being great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…10~6 M), blood vessels contract most strong ly at temperatures between 20 and 35 °C, weakly at temperatures below 20, and weakly also at temperatures above 35 °C. This pattern has been reported for peripheral arteries [5,10,12,18] and central arteries [20], though peripheral veins show a differ ent pattern in which contractile strength is increased by cooling [17].…”
supporting
confidence: 77%
See 1 more Smart Citation
“…10~6 M), blood vessels contract most strong ly at temperatures between 20 and 35 °C, weakly at temperatures below 20, and weakly also at temperatures above 35 °C. This pattern has been reported for peripheral arteries [5,10,12,18] and central arteries [20], though peripheral veins show a differ ent pattern in which contractile strength is increased by cooling [17].…”
supporting
confidence: 77%
“…The fall in arterial responsiveness to NE that occurs during further cooling may result at least in part from nonadrenergic factors, as some investigators have reported that re sponses to the depolarizing action of high-K+ solutions decline in parallel to the decline in responses to NE [ 17,20]. However, though it is possible that reduced a-adrenoceptor af finity may be involved in inhibiting contrac tile responses at temperatures below 20 °C, no studies have measured adrenoceptor af finity at low temperatures.…”
mentioning
confidence: 99%
“…Cooling is known to increase vasoconstrictor tone and prolongs smooth muscle contraction. 6 Therefore, complete closure after cooling can be explained on the basis of increased vasomotor tone and prolonged contraction in the cases with no recordable pulsations. It is, however, more difficult to explain the pressure reduction after cooling, and here one has to think about a delayed opening after reduction of the finger tourniquet pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Toda et al (19) showed that the contractile response of rabbit aortas to vasoconstrictor drugs reached a maximum between 33 and 37°C.…”
mentioning
confidence: 99%